'The Role of Ambidextrous Leadership' Behaviors in Enhancing Organizational Energy': An Analytical Research General AL-Faris Company - Mahmood, Zaid Khawam (Journal of Economics and Administrative Sciences, 2022)
The current research aims to identify the impact of ambidextrous leadership behaviors on organizational energy in Al-Faris Company. The descriptive analytical method was used as a research approach. Adept leadership includes two dimensions (open leadership behaviors and closed leadership behaviors), and organizational energy includes three dimensions (emotional energy, physical energy, and cognitive energy ). The research sample included all the administrative leaders (General Manager, Associate General manager, Department Manager, Division Official  ) in AL-Faris Company / the Iraqi Ministry of Industry. The researcher distributed (74) valid questionnaires after retrieving (53) questionnaires, and the research relied on the statistical package (SPSS). The results indicated that there is a strong effect and a high correlation between the research variables. The most important dimensions of ambidextrous leadership behaviors are open leadership behaviors, which have a high impact on organizational energy. However, there is a weakness in the involvement of individuals in decision-making and the advertising side AL-Faris Company